Analisis Hukum Tentang Poligami Studi Komunikasi Persuasif Pada Masyarakat Madura - Zubair, Asyhari; Azhari, Jalaludin (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2025)
Polygamy is one of the outstanding issues in Islamic family law that must be addressed and investigated. In the Islamic community, polemics at a particular level of debate frequently end without reaching an agreement. This behaviour surely promotes a variety of issues, ranging from the collapse of harmony to divorce. You may fix this difficulty by using persuasive communication. The purpose of this study is to look at the efforts married couples take to develop and maintain a sense of harmony and comfort in their home. Husbands employ models and concepts to overcome challenges following polygamy. This study is based on descriptive qualitative research, which collects data through observation, interviews, and documentation. The findings of this study suggest that husbands try a variety of methods, such as persuading and giving confidence to their wives, creating a stamped memorandum of agreement, seeking guidance, direction, advice, and blessing prayers from credible religious figures, and persuading wives about the fate of their children in the future during their marriage. decorated with disagreements, quarrels, and quarrels that led to divorce. This research employs the probabilistic model and the hope principle.